Perna viridis (L.) 1758 as the correct name for the Southeast Asian green mussel (Bivalvia Mytilidae) - Young, Adam L.; Yap, Wilfredo G. (1984)
The Southeast Asian green mussel is perna viridis. The wide separation of the retractor muscle scars in the adult shell and the special set of teeth on the posterior shoulder of the larval shell definitely the green mussel under the genus perna retzius.
Includes bibliographical references (pages 4-5)
Keywords: Myersophis -- Description; Psammodynastes -- Description; Zoology; Perna viridis -- Revision of name; Mussels, Green -- Description